From the low deciduous forest to the traditional silvopastoral system in the Sierra de Huautla, Morelos - Cruz León, Artemio; Cruz Aguilar, Ranulfo (Revista Mexicana de Ciencias Agrícolas, 2020)
Currently, the Sierra de Huautla Biosphere Reserve (Rebiosh) is considered the last conserved stronghold of the low deciduous forest (SBC) of Mexico. In this document this approach is discussed and proposed as a traditional agroecosystem with silvopastoral management, with historical development and antecedents of use prior to the arrival of cattle in colonial times and a current animal load above technical parameters, in addition to other parameters that support the creation of an agroecosystem whose ecological behavior is close to the SBC. This situation is complicated by the creation of the Rebiosh, whose management plan ignores the traditional use of native usufructuaries and restrictions and criminalization are applied to traditional users; without considering alternative ways of meeting the needs not covered by the provisions of the protected natural area. The operation of the traditional silvopastoral system is described and it is concluded with the need to deepen its understanding, which allows, through participatory processes, the construction of resources that strengthen traditional agroforestry systems and the vision of the users to include in the Plan of Handling the Rebiosh.
Keywords: Biosphere reserve; protected natural area; traditional silvopastoral systems